2022
DOI: 10.3389/fpsyg.2022.978913
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between dietary score and depression in cancer patients: Data from the 2005–2018 National Health and Nutrition Examination Surveys

Abstract: AimTo investigate the correlation between dietary score and depression in patients with cancer.MethodsIn this cross-sectional study, data were collected from the National Health and Nutrition Examination Survey (NHANES) 2005–2018, a cross-sectional and nationally representative database, to compare 322 patients with depression to 2,868 with no depression. Mediterranean (MEDS) diet, Dietary Approaches to Stop Hypertension (DASH) diet, and the Healthy Eating Index 2015 (HEI-2015) score were calculated. Depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Breast cancer survivors report reduced cancer-related fatigue if their food is of higher quality after diagnosis [ 188 ]. In this regard, a new research study has shown links between nutrition, mental health, and cancer, and it found that cancer patients with Mediterranean diet patterns had a lower incidence of depression ( Figure 3 ) [ 189 ]. Nevertheless, in order to provide treatment recommendations based on these findings, more research is needed.…”
Section: Impact Of Dietary Practices On Healthmentioning
confidence: 99%
“…Breast cancer survivors report reduced cancer-related fatigue if their food is of higher quality after diagnosis [ 188 ]. In this regard, a new research study has shown links between nutrition, mental health, and cancer, and it found that cancer patients with Mediterranean diet patterns had a lower incidence of depression ( Figure 3 ) [ 189 ]. Nevertheless, in order to provide treatment recommendations based on these findings, more research is needed.…”
Section: Impact Of Dietary Practices On Healthmentioning
confidence: 99%
“…According to the age distribution, the participants were divided into three groups: first (20–29 years), second (30–40 years), and third (41–54 years) tertiles. Marital status was defined as married, divorced, separated, or spinster 20 . The participants’ educational level was recorded as less than high school, high school, or college and above 21 .…”
Section: Methodsmentioning
confidence: 99%
“…Another randomized, double-blind, placebo-controlled clinical trial focusing on adolescents who consumed a daily supplement of wild blueberry (containing approximately 253 mg anthocyanidins) found that compared to the placebo group, participants receiving anthocyanidin supplements had significantly reduced self-reported depressive symptoms (P = 0.02, 95%CI: (-6.71,-5.35)] [28]. Previous cross-sectional studies have also demonstrated that correlation between higher diet quality, as indicated by higher scores on the Healthy Eating Index HEI2015), and a lower risk of depression [29][30][31]. Our study further confirms this association [46.09 (0.66) vs. 50.85 (0.47), P<0.0001].…”
Section: Table 2 Differences In Flavonoid Content Between the Depress...mentioning
confidence: 99%